PENGGUNAAN E-MODUL INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP PADA MATERI KALOR - Windi Nur Aeni; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to describe the implementation of the learning process, improved learning outcomes and student responses to the use of interactive e-modules in heat material in learning. This study is a pre-experiments study, using one group pretest-posttest design. The study was conducted on 32 students from class VII-H SMPN 5 Gresik. Sample selection uses random sampling techniques. Data collection methods used in the form of observations, tests and questionnaires. The results of the data collection will be analyzed using mode values to measure learning performance, normality tests and paired t-tests to measure the significance of improved learning outcomes, calculate N-Gain scores, and calculate percentage averages in each aspect of the questionnaire to measure students' response to learning. The results of this study obtained that, the learning process has been carried out in a very good category. Student activity increased at the second meeting, which was 75% with a high category. Obtained the average N-gain value of students in one class of 0.65, so that it can be expressed in the moderate category. Learning outcomes experienced a significant increase, as they gained a value significance of 0,000<0.05. Judging from the results of the response, 96.35% of students gave a positive response to the learning process. The conclusion of this study is that the use of interactive e-modules on heat material can improve learning outcomes for students of class VII-H SMPN 5 Gresik.